Buying a business - Tyson, Eric (Eric Kevin); Schell, Jim (--For dummies., 2024)
Buying a Business For Dummies guides you through the process of becoming an entrepreneur without starting from scratch. Before you purchase an existing business, you'll need to know what types of opportunities are out there, how to identify the right fit for your goals, and which strategies to use as you negotiate the deal and manage a smooth transition. This book gives you step-by-step advice on all of that. What about actually running the business successfully? You're covered there, too, with clear information on executing a smooth ownership transition and growing your new business. Let this friendly Dummies guide be your mentor as you embark on your business ownership adventure.